Physic-environmental diagnosis of coffee crop in the State of Minas Gerais, Brazil - Bernardes, Tiago; Moreira, Maurício Alves; Adami, Marcos; Rudorff, Bernardo Friedrich Theodor (Coffee Science - ISSN 1984-3909, 2012)
The State of Minas Gerais is the major coffee producer in Brazil. The crop is spread over different environments as wellas different management systems. Knowledge about environmental variables helps to establish and define appropriate managementpractices for the coffee crop. The objective of this study was to access spatially and quantitatively the occupation of coffee crop in MinasGerais and to elaborate a land use model for coffee crop in the state taking into account variables such as soil type, altitude, slope andaspect. We have used remote sensing data to map coffee areas and to derive relief data (altitude, slope and aspect). The relief data anda digital soil map were overlapped with the coffee area map in order to access the prevailing relationships. We have also consideredthe most favorable classes of each theme to determine the most suitable environment for coffee crop. Results show that the crop isdistributed within altitudes varying from 500 to 1.200 m. There are coffee fields in all classes of slope but slopes up to 15%predominate. The aspect does not seem to influence the occurrence of coffee since the proportions of coffee fields are about the samein all classes. However, we have found a slightly smaller proportion of coffee placed in west-facing slopes. In relation to soil types,Latossolos and Argissolos are the most occupied with coffee, that is, up to 80% of coffee fields are placed in those soils. About 70%of coffee fields are spread in appropriate environments over the best classes of soil, altitude, slope and aspect.